Association between disease extent and pain symptoms in patients with deep infiltrating endometriosis. Issue 5 (November 2019) - Montanari, Eliana; Dauser, Bernhard; Keckstein, Joerg; Kirchner, Elisabeth; Nemeth, Zoltan; Hudelist, Gernot
Abstract: Research question: The study aimed to assess the associations between pre-operative symptoms in patients with deep infiltrating endometriosis (DIE) and intraoperatively determined extent of disease as described by the revised ENZIAN score. Design: This was a retrospective data analysis of women who underwent surgery for DIE between 2014 and 2018 at the Department of Gynecology, Hospital St. John of God, Vienna (a tertiary referral centre for endometriosis). Results: Data from 245 women were analysed. Statistically significant associations were found between involvement of ENZIAN compartment B (uterosacral ligaments, parametrium) and presence of dyspareunia ( P  = 0.002), ENZIAN compartment C (rectum, sigmoid colon) and dyschezia ( P < 0.001), and ENZIAN compartment FB (urinary bladder) and dysuria ( P < 0.001, Fisher's exact test). Statistically significant correlations were also detected between symptom severity of dyschezia and lesion size in ENZIAN compartment C ( r s  = 0.334, P < 0.001), and severity of dyspareunia and lesion size in ENZIAN compartment B ( r s  = 0.127, P  = 0.046). Severity of dysmenorrhoea was correlated with lesion size in ENZIAN compartment A ( r s  = 0.244, P < 0.001) and was associated with the presence of adenomyosis (compartment FA; P  = 0.005, Mann–Whitney U -test). Additionally, the number of affected compartments (A, B, C and FA) correlated with the severity of dysmenorrhoea ( r s  = 0.256, P < 0.001) and dyschezia ( r s  = 0.161, P  = 0.012). Conclusion: In contrast to previous studies evaluating disease extent based on the revised American Society for Reproductive Medicine (rASRM) score, disease localization and extent as described by the revised ENZIAN score was associated and correlated with the presence and severity of different pre-operative symptoms. These explorative findings suggest that it may be important to evaluate the extent of DIE using the revised ENZIAN score in addition to the rASRM score.